PEMIKIRAN PENDIDIKAN SAYYID IDRUS BIN SALIM ALJUFRI DALAM PEMBENTUKAN AKHLAK ISLAMI - Nurhayati, Nurhayati (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2018)
This paper discusses in depth the nature of the educational thoughts of Sayyid Idrus bin Salim Aljufri in the effort to establish Islamic morality in the midst of people experiencing moral disturbances both theologically and sociologically. Using descriptive-analytical methods, this discussion concludes that the nature of educational thought Sayyid Idrus bin Salim Aljufri is an attempt to comprehensively educate all the potential that exists in man himself, including: reason, morality, spiritual and social, and it is done continuously because education is a process that humans must go through throughout their lives. To maintain the educational thinking that he had built, Sayyid Idrus bin Salim Aljufri carried out the development passed by the Educational Institution Alkhairaat, in general it could be described in three aspects, namely: institutional aspects, organizational aspects and aspects of the curriculum. Thus it will form Islamic moral values ​​in the midst of society such as: adherence to rules, especially rules that have been outlined by God Almighty, mutual respect for ma’ruf and nahi mungkar, invite each other to do good deeds, show identity as a Muslim. It is all inseparable from the method of education approved by Sayyid Idrus bin Salim Aljufri through the integration between science and morals and the nature of Washathiyah or tawazun / moderate